Perancangan Antena Mikrostrip Quasi-Yagi Untuk Aplikasi Wigig 60 GHZ - Septyo Adi Pratama; Yusnita Rahayu; Adit Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
WiGig (Wireless Gigabite) is the next generation technology of WiFi (Wireless Fidelity). WiGig speeds can reach 7Gbps / s and have great access. In this study, microstrip antenna Quasi-Yagi MIMO (Multiple Input Multiple Output) High gain for WiGig application operating at 60 GHz is discussed. Microstrip antenna is designed by using MIMO Technique to increase the gain. Antenna is simulated by using CST (Computer Simulation Technology) Microwave Studio software. From the simulation results, the antenna can operate at a frequency of 60 GHz. The bandwidth obtained is 3.75 GHz (5.79%) at VSWR 1.04 and the gain is 10.1 dB.Keyword: WiGig, MIMO, Gain, Bandwidth, VSWR